Spiritualty based on the Roy Adaptation Model for Use in Practice, Teaching and Research - Callista Roy (Universidad de La Sabana, 2018)
Espiritualidad basada en el Modelo de Adaptación de Roy para uso en la práctica, la enseñanza y la investigación Espiritualidade baseada no Modelo de Adaptação de Roy para uso na prática, ensino e pesquisa In today's fast-paced and complex world, the need for spiritualty is greater than ever. The Roy Adaptation Model (RAM) provides a strong basis for spiritualty. Spirituality allows us to look beyond the material world to have a central experience of seeking a higher power. This seeking is related to the essence of the person and their relationships with others. Through spirituality, we search for fulfillment, meaning and purpose in life. The RAM reflects spiritualty as rooted in the philosophical assumption of veritivity that sees truth in a creator with principles of unity, diversity and self-expression reflected in all of creation, the earth and in people. People have a basic need for spiritualty. According to the model, spirituality is an influencing factor or stimulus for all adaptive behavior. Spirituality is also a strategy for coping and adapting. Common human spiritual experiences are wonder, awe and gratitude for life, along with acknowledgement of human dependence, finitude and interdependence... To reference this editorial / Para citar esta editorial / Para citar este artigo Roy C. Spiritualty Based on the Roy Adaptation Model for Use in Practice, Teaching and Research. Aquichan 2018: 18(4); 393-4. DOI: 10.5294/aqui.2018.18.4.1